Effects of phytosterol-rich foods on lipid profile and inflammatory markers in patients with hyperlipidemia: a systematic review and meta-analysis - Zhang, Yihua; Zhang, Qian; Wang, Xiumei; Jia, Yatian; Niu, Qingmei; Ding, Shuo; Li, Wenjing (Frontiers in Pharmacology, 2025)
BackgroundAs naturally occurring compounds in plant-based foods, phytosterols have attracted attention for their lipid-modulating potential and proposed role as adjunctive therapies in managing hyperlipidemia. Nevertheless, conflicting evidence persists regarding their dual impact on dyslipidemia and subclinical inflammation.ObjectiveThis systematic review aimed to assess the impact of phytosterol-rich foods on lipid metabolism and inflammatory responses in hyperlipidemic populations.MethodsA thorough literature search was performed across nine databases (including China National Knowledge Infrastructure Wanfang Data, VIP, SinoMed, PubMed, Cochrane Library, Embase, Scopus, Web of Science) from their inception up to 15 February 2025. Studies included were randomized controlled trials evaluating phytosterol interventions in adults with hyperlipidemia. The quality of the included studies was evaluated using the Cochrane Randomized Trial Risk Bias Tool, and Data analysis was performed using RevMan 5.4.ResultsThis study included 14 randomized controlled trials with a total of 1,088 participants. The pooled results demonstrated statistically significant reductions in total cholesterol (TC) levels (mean difference (MD) = −0.65, 95% CI −0.83 to −0.47, P < 0.00001) and low-density lipoprotein cholesterol (LDL-C) levels (MD = −0.52, 95% CI −0.66 to −0.38, P < 0.00001), along with a modest increase in high-density lipoprotein cholesterol (HDL-C) levels (MD = 0.08, 95% CI 0.05 to 0.10, P < 0.00001). No significant change was observed for C-reactive protein (CRP) levels (MD = −0.00, 95% CI −0.01 to 0.00, P = 0.32). Although a borderline significant reduction in triglycerides (TG) levels was noted (MD = −0.24, 95% CI −0.47 to −0.01, P = 0.04), this finding displayed considerable heterogeneity.ConclusionPhytosterol intervention demonstrates significant efficacy in modulating atherogenic lipid profiles, such as TC and LDL-C, while also elevating HDL-C levels in individuals with hyperlipidemia. Yet, it fails to demonstrate anti-inflammatory activity as measured by CRP levels. The observed marginal TG-lowering effect should be interpreted with caution given substantial interstudy heterogeneity. Therefore, larger, metabolomics-inclusive studies are required for definitive conclusions and clinical guidance.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#loginpage, identifier CRD420251002645.